The role of [(68) Ga]Ga-DOTATATE PET/CT in wild-type KIT/PDGFRA gastrointestinal stromal tumours (GIST) - Aloj, Luigi (EJNMMI Res, 2021)
BACKGROUND: [(68) Ga]Ga-DOTATATE PET/CT is now recognised as the most sensitive functional imaging modality for the diagnosis of well-differentiated neuroendocrine tumours (NET) and can inform treatment with peptide receptor radionuclide therapy with [(177)Lu]Lu-DOTATATE. However, somatostatin receptor (SSTR) expression is not unique to NET, and therefore, [(68) Ga]Ga-DOTATATE PET/CT may have oncological application in other tumours. Molecular profiling of gastrointestinal stromal tumours that lack activating somatic mutations in KIT or PDGFRA or so-called ‘wild-type’ GIST (wtGIST) has demonstrated that wtGIST and NET have overlapping molecular features and has encouraged exploration of shared therapeutic targets, due to a lack of effective therapies currently available for metastatic wtGIST. AIMS: To investigate (i) the diagnostic role of [(68) Ga]Ga-DOTATATE PET/CT; and, (ii) to investigate the potential of this imaging modality to guide treatment with [(177)Lu]Lu-DOTATATE in patients with wtGIST. METHODS: [(68) Ga]Ga-DOTATATE PET/CT was performed on 11 patients with confirmed or metastatic wtGIST and one patient with a history of wtGIST and a mediastinal mass suspicious for metastatic wtGIST, who was subsequently diagnosed with a metachronous mediastinal paraganglioma. Tumour expression of somatostatin receptor subtype 2 (SSTR2) using immunohistochemistry was performed on 54 tumour samples including samples from 8/12 (66.6%) patients who took part in the imaging study and 46 tumour samples from individuals not included in the imaging study. RESULTS: [(68) Ga]Ga-DOTATATE PET/CT imaging was negative, demonstrating that liver metastases had lower uptake than background liver for nine cases (9/12 cases, 75%) and heterogeneous uptake of somatostatin tracer was noted for two cases (16.6%) of wtGIST. However, [(68) Ga]Ga-DOTATATE PET/CT demonstrated intense tracer uptake in a synchronous paraganglioma in one case and a metachronous paraganglioma in another case with wtGIST. CONCLUSIONS: Our data suggest that SSTR2 is not a diagnostic or therapeutic target in wtGIST. [(68) Ga]Ga-DOTATATE PET/CT may have specific diagnostic utility in differentiating wtGIST from other primary tumours such as paraganglioma in patients with sporadic and hereditary forms of wtGIST.